Respuesta :
Answer:
(x, y) =(2,-3)
Step-by-step explanation:
4x+3y=-1
3x-9y=33 /:3
4x+3y=-1.....(1)
x-3y=11... (2)
(1)+(2): 5x=10
x-3y=11
x=10/5
x-3y=11
x=2
2-3y=11
x=2
-3y=11-2
x=2
-3y=9
x=2
y=9/(-3)
x=2
y=-3
(x,y)=(2,-3)
Answer:
(2 , -3)
Step-by-step explanation:
4x + 3y = –1
3x – 9y = 33
12x + 9y = –3 (1)
3x – 9y = 33 (2)
We add equation (1) and (2)
12x + 9y = –3
+
3x – 9y = 33
___________
15x + 0 = 30
then x = 30/15 = 2
if we substitute x by 2 in equation (2) we get :
3(2) – 9y = 33 ⇒ 6 - 9y = 33 ⇒ -9y = 33 - 6 = 27⇒ y = 27/-9 = -3
finally, x = 2 and y = -3.
:)